2020
DOI: 10.1186/s13031-020-00294-w
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of hygiene kits during a cholera outbreak in Kasaï-Oriental, Democratic Republic of Congo: a process evaluation

Abstract: Background: Cholera remains a leading cause of infectious disease outbreaks globally, and a major public health threat in complex emergencies. Hygiene kits distributed to cholera case-households have previously shown an effect in reducing cholera incidence and are recommended by Médecins Sans Frontières (MSF) for distribution to admitted patients and accompanying household members upon admission to health care facilities (HCFs). Methods: This process evaluation documented the implementation, participant respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 68 publications
(99 reference statements)
1
34
0
1
Order By: Relevance
“…Hygiene kits aim to reduce the risk of disease transmission by encouraging the increased practice of hygiene behaviours at the household level. However, there is limited evidence about the acceptability of hygiene kits, the use of hygiene kit products by crisis-affected populations and the effect of hygiene kit distributions on behaviour or health outcomes [ 13 , 15 , 21 23 ]. The available evidence is predominantly focused upon soap and hygiene kit distributions in camp settings or cholera outbreaks, and has documented mixed results [ 13 , 22 , 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hygiene kits aim to reduce the risk of disease transmission by encouraging the increased practice of hygiene behaviours at the household level. However, there is limited evidence about the acceptability of hygiene kits, the use of hygiene kit products by crisis-affected populations and the effect of hygiene kit distributions on behaviour or health outcomes [ 13 , 15 , 21 23 ]. The available evidence is predominantly focused upon soap and hygiene kit distributions in camp settings or cholera outbreaks, and has documented mixed results [ 13 , 22 , 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study in Bangladesh distributed hygiene kits to cholera cases upon discharge from treatment centres and showed promising impacts on behaviour and health outcomes [ 24 ]. The majority of other studies have focused on the feasibility of distributing hygiene kits, highlighting the challenges achieving sufficient coverage of the population [ 23 , 27 ]. Many of the studies of soap and hygiene kit distributions rely on self-reported measures or proxy measures of product use and behaviour [ 21 , 27 , 28 ], which are considered less reliable indicators of handwashing behaviour [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on recent studies, effective targeting interventions in hotspots could eliminate up to 50% of cases in Sub-Saharan Africa ( 11 ). Among the few studies available, D'Mello-Guyett et al ( 12 ) underline how the distribution of hygiene kits is a promising form of intervention for cholera control and that the integration of a WASH intervention at the point of admission of suspected cases is new in cholera control efforts, particularly in outbreaks and complex emergencies ( 12 ). Even though the relationship between cholera and Water, Sanitation, and Hygiene (WASH) has long been established ( 13 ), the beneficial impact of water and sanitation projects like CLTS, specifically in cholera hotspots, is often challenged due to the lack of evidence and the complexity in demonstrating such an impact (e.g., long-term implementation of WASH projects, availability of data, sustainability of WASH projects) ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…One study in Bangladesh distributed hygiene kits to cholera cases upon discharge from treatment centres and showed promising impacts on behaviour and health outcomes (24). The majority of other studies have focused on the feasibility of distributing hygiene kits, highlighting challenges with achieving su cient coverage of the population (23,27).…”
mentioning
confidence: 99%
“…However, there is limited evidence about the acceptability of hygiene kits, the use of hygiene kit products by crisis-affected populations and the effect of hygiene kit distributions on behaviour or health outcomes (13,15,(21)(22)(23). Available evidence has predominantly focused on soap or hygiene kit distributions in camp settings or during cholera outbreaks and has documented mixed results (13,22,(24)(25)(26).…”
mentioning
confidence: 99%